High-performance autoclaved aerated concrete and preparation process thereof
By optimizing the raw material ratio and process flow, high-performance autoclaved aerated concrete is formed, which solves the problems of loose structure and low compressive strength of tobemollite crystals in the prior art, and achieves high compressive strength and good thermal insulation performance.
Patent Information
- Application Number
- CN202510388899.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-31
AI Technical Summary
The existing autoclaved aerated concrete has loose crystal structure, insufficient mechanical properties, poor pore uniformity formed by the foaming process and low compressive strength, which limits its application in high-rise buildings.
By optimizing the ratio of raw materials, high-performance autoclaved aerated concrete is composed of quartz sand, quicklime, cement, foaming agent, boronite powder, glass powder and foam stabilizer. Combined with pretreatment and coating technology, the performance of raw materials is improved, and a uniform bubble structure is formed through specific molding and steaming processes.
The compressive strength and strength-density ratio of concrete are improved, and the insulation and sound insulation properties of the material are enhanced. The prepared concrete has a small dry density, which is suitable for high-rise buildings.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, in particular to high-performance autoclaved aerated concrete and a preparation process thereof. Background Art
[0002] Autoclaved aerated concrete (AAC) is widely used in the construction industry due to its light weight, heat preservation, and sound insulation properties. Traditional autoclaved aerated concrete uses siliceous materials (such as quartz sand) and calcium materials (such as cement and quicklime) as the matrix, forms a porous structure through aluminum powder foaming, and then generates Tobermorite crystals through autoclaving and curing. However, the existing technology has the following problems: Tobermorite has a loose crystal structure, resulting in insufficient mechanical properties; The pores formed by the foaming process have poor uniformity, and large-diameter pores easily become stress concentration points; the compressive strength is generally lower than 5MPa, which limits its application in high-rise buildings. Summary of the invention
[0003] The object of the present invention is to provide a high-performance autoclaved aerated concrete and a preparation process, so that the prepared concrete has a lower dry density, higher compressive strength and a high strength-density ratio.
[0004] To achieve the above object, the present invention provides the following technical solutions: The high-performance autoclaved aerated concrete comprises the following raw materials in parts by weight: 25-35 parts of quartz sand, 18-22 parts of quicklime, 12-18 parts of cement, 3-5 parts of foaming agent, 5-8 parts of colemanite powder, 0.1-0.3 parts of foam stabilizer and appropriate amount of water, with a water-cement ratio of 0.5-0.55, and the foaming agent is aluminum powder and silicon powder in a mass ratio of 3: (4-5).
[0005] Preferably, the foaming agent is aluminum powder and silicon powder in a mass ratio of 3:5. Aluminum powder pretreatment: take aluminum powder with a particle size of 50-100μm, then coat the aluminum powder with aluminum phosphate sol, dry it, and the coating layer thickness is 1-2μm; silicon powder pretreatment: wash and dry it with a 5% hydrochloric acid solution, then ball mill it to a particle size less than 200nm, and the volume ratio of silicon powder to hydrochloric acid solution is 0.5.
[0006] Preferably, the quicklime particle size is 50-100 μm, and 30-40% of the quicklime is modified: the quicklime is coated with stearic acid and dried, and the coating layer thickness is 1-2 μm; the colemanite powder is selected to have a particle size of 5-15 μm, and then coated with a silane coupling agent, dried, and the coating layer thickness is 0.5-1 μm.
[0007] Preferably, the cement is sulphoaluminate cement.
[0008] Preferably, 5-10 parts of glass powder with a particle size of ≤10 μm are included.
[0009] Preferably, the foam stabilizer is sodium lauryl sulfate, hydroxypropyl methylcellulose and nano-SiO2 in a mass ratio of 1:0.5:0.4.
[0010] Preferably, the raw materials include the following parts by weight: 30 parts of quartz sand, 20 parts of quicklime, 15 parts of cement, 4.0 parts of foaming agent, 6.0 parts of calcium borate powder, 8.0 parts of glass powder, 0.2 parts of foam stabilizer and appropriate amount of water, with a water-cement ratio of 0.52.
[0011] Preferably, the aluminum phosphate sol is prepared by the following method: aluminum sulfate Al2(SO4)3 and sodium dihydrogen phosphate NaH2PO4 are used in a molar ratio of 1:6 to prepare an aluminum sulfate solution and a sodium dihydrogen phosphate aqueous solution respectively, and the sodium dihydrogen phosphate solution is slowly added dropwise to the aluminum sulfate solution while stirring, and the pH value of the reaction system is controlled between 3-5 for 1 hour, aged for 12 hours, and then washed and filtered with water to obtain aluminum phosphate sol.
[0012] The high-performance autoclaved aerated concrete preparation process of the present invention comprises the following steps: (1) raw material pretreatment: pre-wetting quartz sand to a moisture content of 8-12%, and activating colemanite powder at 105° C. for 2 hours; (2) mixing: mixing all raw materials to obtain slurry; (3) molding: pouring the slurry into a mold and standing it at 82-85° C. for 2 hours, demolding and cutting to form; and (4) steam curing: steam curing the cut product under high pressure.
[0013] Preferably, the step (2) mixing is as follows: quartz sand, quicklime, cement, glass powder and colemanite are added in sequence, dry-mixed for 5 minutes, silicon powder, foam stabilizer and water are added, wet-mixed for 8-10 minutes, allowed to stand for 0.5 hour, and aluminum powder is added and wet-mixed for 5-8 minutes to obtain slurry; the step (4) steam curing is as follows: the cut product is sent to a steam curing chamber and heated to 205°C at 30-40°C / h, maintained at a constant temperature for 8 hours at a pressure of 1.52-1.55 MPa, and then cooled to room temperature at a rate of 12-13°C / h.
[0014] The mechanism of action of the present invention: Quartz sand is the main source of silicon in concrete. In concrete, it serves as a skeleton material, providing support for other components and enhancing the overall structural stability of concrete. At the same time, it participates in hydration reactions and reacts with other substances to generate cementitious products, which helps to improve the strength of concrete. Quicklime is an important source of calcium. In concrete, quicklime reacts with water to generate calcium hydroxide, which provides an alkaline environment for subsequent hydration reactions and promotes the hydration of other cementitious materials. Among them, quicklime modified by stearic acid coating can slow down its hydration rate, avoid excessive reaction in the early stage, and ensure the working performance of concrete during mixing and molding.
[0015] Aluminum powder and silica powder react with water in an alkaline environment to produce hydrogen, which creates pores inside the concrete, thereby reducing the weight of the concrete and achieving lightweight. Since the aluminum powder is coated with aluminum phosphate sol and the addition time of the aluminum powder is controlled during mixing, its participation in gasification can be delayed. Compared with ordinary silicate cement, sulphoaluminate cement has a lower pH value and relatively delays the gasification effect. Some quicklime that is not coated with stearic acid first reacts with water to produce calcium hydroxide and releases a large amount of heat, providing conditions for silica powder to produce gas. Silica powder produces gas. Since the amount of gas emitted by silica powder is small, it first produces dense small bubbles in the concrete, and then the coated quicklime continues to hydrolyze and releases heat and provides alkaline conditions for aluminum powder to produce gas. Aluminum powder A large number of relatively large bubbles will be generated during the high temperature and high pressure steaming stage. Sodium dodecyl sulfate, as a surfactant, can reduce the surface tension of the gas-liquid interface, making bubbles easier to form and stabilize; Hydroxypropyl methylcellulose has thickening and water-retaining effects, which can increase the strength and stability of the bubble liquid film; Nano-SiO2 can fill the surface of the bubbles, enhance the stability of the bubbles, prevent the bubbles from merging and bursting, and ensure the uniformity of the bubble structure inside the concrete, so that the formed concrete forms a structure in which evenly distributed large bubbles dominate and small bubbles are densely distributed in the gaps between large bubbles.
[0016] Colemanite powder: Colemanite decomposes into calcium oxide (CaO) and boron oxide (B2O3) in a high temperature and high pressure steam curing environment. The latter dissolves in an alkaline solution to form boric acid (H3BO3), which further dissociates into boron ions (B 3+ ), B produced by the decomposition of colemanite 3+ Ions diffuse into the tobermorite crystal structure, B 3+ The radius is smaller, partially replacing the Si in the silicon-oxygen tetrahedron in the tobermorite crystal 4+ , forming a tighter BO-Si bond; the other part B 3+ Enter the crystal interlayer and interact with calcium ions (Ca 2+ ) combine to form composite ions, compress the interlayer distance, optimize the crystal structure, and thus significantly improve the compressive strength of concrete. At the same time, with the micro-aggregate filling effect of glass powder, it can fill the pores inside the concrete, improve the density of the concrete, reduce the porosity, and thus enhance the strength of the concrete. The use of coated colemanite powder can improve the interface compatibility of colemanite with quartz stone, cement, foam stabilizer and other ingredients, and improve the uniformity of the overall system.
[0017] Compared with the prior art, the present invention has the following beneficial effects: the present invention has high strength and lightweight performance, and through reasonable allocation of raw materials such as quartz sand, quicklime, cement, etc., and optimization of the crystal structure with colemanite powder, the synergistic effect of aluminum powder and silicon powder in the foaming agent, combined with the foam stabilizer to stabilize the bubbles, a reasonable bubble structure with a gradient distribution of large bubbles and small bubbles is formed inside the concrete, thereby improving the thermal insulation and sound insulation performance of the material, and the prepared concrete has a small dry density, a high compressive strength, and a high strength-density ratio. DETAILED DESCRIPTION
[0018] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0019] The high-performance autoclaved aerated concrete in the following embodiments includes the following raw materials: quartz sand, quicklime, cement, foaming agent, calcium borate powder, glass powder, foam stabilizer and appropriate amount of water, with a water-cement ratio of 0.52, wherein the water-cement ratio in the present invention refers to the weight ratio of the amount of water to the amount of ash, wherein the amount of ash is the total mass of cement and quicklime.
[0020] The foaming agent is aluminum powder and silicon powder in a mass ratio of 3:5. Aluminum powder pretreatment: take aluminum powder with a particle size of 50-100μm, then coat the aluminum powder with aluminum phosphate sol, dry it, and the coating layer thickness is 1-2μm; silicon powder pretreatment: wash and dry it with a 5% hydrochloric acid solution, then ball mill it to a particle size of less than 200nm, and the volume ratio of silicon powder to hydrochloric acid solution is 0.5.
[0021] The quicklime particle size is 50-100μm, and 40% of the quicklime is modified: the quicklime is coated with stearic acid and dried, and the coating thickness is 1-2μm; the colemanite powder is selected to have a particle size of 5-15μm, and then coated with a silane coupling agent, dried, and the coating thickness is 0.5-1μm.
[0022] Aluminum phosphate sol was prepared by the following method: Raw materials: aluminum sulfate Al2(SO4)3 and sodium dihydrogen phosphate NaH2PO4 in a molar ratio of 1:6, both are analytically pure reagents. Reaction process: prepare aluminum sulfate solution and sodium dihydrogen phosphate aqueous solution respectively, add water twice the amount of water required for complete dissolution, slowly drop the sodium dihydrogen phosphate solution into the aluminum sulfate solution, stirring while dropping, the reaction equation is: (Al2(SO4)3+6NaH2PO4=2Al(H2PO4)3+3Na2SO4; The reaction temperature is controlled at 75-80° C. During the dropping process, the pH value of the reaction system is controlled between 3-5 by dropping sodium hydroxide or hydrochloric acid solution, reacting for 1 hour, aging for 12 hours, and then washing and filtering with water to obtain aluminum phosphate sol.
[0023] Method for coating aluminum powder with aluminum phosphate sol: add aluminum powder to an appropriate amount of deionized water at 20-25°C, and ultrasonically disperse for 10-30 minutes to evenly disperse the aluminum powder in the water to form a suspension. Slowly add aluminum phosphate sol to the aluminum powder suspension, stir for 2 hours, age for 12 hours, and then wash and filter with deionized water to obtain.
[0024] The method of stearic acid coating quicklime is as follows: stearic acid is fully dissolved in anhydrous ethanol, quicklime is added, stirred at 65-70° C. for 2 hours, aged for 12 hours, and then washed and filtered with anhydrous ethanol to obtain.
[0025] The cement used is sulphoaluminate cement.
[0026] The foam stabilizer is a compound of sodium lauryl sulfate, hydroxypropyl methylcellulose and nano-SiO2 in a mass ratio of 1:0.5:0.4.
[0027] The following embodiments provide a method for preparing high-performance autoclaved aerated concrete: comprising the following steps: (1) raw material pretreatment: pre-wetting quartz sand to a moisture content of 10% (the water used is included in the water-cement ratio), and activating colemanite powder at 105° C. for 2 hours; (2) mixing: adding quartz sand, quicklime, cement, glass powder, and colemanite in sequence, dry mixing for 5 minutes, adding silicon powder, foam stabilizer, and water, wet mixing for 8-10 minutes, standing for 0.5 hours, and then adding aluminum powder and wet mixing for 5-8 minutes to obtain a slurry; (3) molding: pouring the slurry into a mold and standing at 82-85° C. for 2 hours, demolding and cutting to shape; (4) curing: sending the cut product into a curing chamber and heating it to 205° C. at 30-40° C. / h, keeping it at a constant temperature for 8 hours at a pressure of 1.52-1.55 MPa, and then cooling it to room temperature at a rate of 12-13° C. / h.
[0028] The raw materials adopted in the present invention are: Quartz sand, particle size 0.25-0.5mm, SiO2 mass content ≥98%.
[0029] Quicklime: quicklime with CaO mass content ≥98%.
[0030] Silicon powder refers to elemental silicon powder, and aluminum powder refers to elemental aluminum powder.
[0031] Sulphoaluminate cement: High-belite sulphoaluminate cement purchased from Nanjing Leputai New Material Technology Co., Ltd., strength grade: 42.5.
[0032] Boronite powder: purchased from Dalian Wobiwo Mining Co., Ltd., Ca2B6O 11 5H2O mass content ≥98%.
[0033] Glass micropowder: Shijiazhuang Jihandong New Material Technology Co., Ltd. JHD-0058 model glass micropowder, particle size 2000 mesh.
[0034] Sodium lauryl sulfate: purchased from Shaoxing Zhe Chuang Chemical Co., Ltd. Zhe Chuang brand K12 sodium lauryl sulfate.
[0035] Hydroxypropyl methylcellulose: purchased from Shanghai Chenqi Chemical Technology Co., Ltd., model HPMC-75,000-100,000 viscosity.
[0036] Nano-SiO2: purchased from Xuzhou Jie Innovation Material Technology Co., Ltd., brand: Hongwu, CAS: 7631869.
[0037] Stearic acid: purchased from Jiangyin Zhuoqi Trading Co., Ltd., brand and model: Kangqiao 1842.
[0038] Silane coupling agent: Silane coupling agent KH-560 produced by Dongguan Shanyi Plastic Chemical Co., Ltd. was used.
[0039] The embodiments of the present invention use the components in Table 1 (in parts by weight): Table 1
[0040] The reference examples of the present invention are: The difference between Control Example 1 and Example 1 is that the foaming agent is aluminum powder with a particle size of 50-100 μm.
[0041] The difference between Control Example 2 and Example 1 is that the foaming agent is aluminum powder and silicon powder in a mass ratio of 4:5, the particle size of the aluminum powder is 50-100 μm, the particle size of the silicon powder is less than 200 nm, and the aluminum powder and silicon powder are not pretreated.
[0042] The difference between Control Example 3 and Example 1 is that the colemanite is replaced by an equal amount of quartz sand.
[0043] The difference between Comparative Example 4 and Example 1 is that sodium lauryl sulfate is used as the foam stabilizer.
[0044] The difference between Comparative Example 5 and Example 1 is that ordinary Portland cement is used as cement.
[0045] The difference between Comparative Example 6 and Example 1 is that the quicklime is not subjected to sexual treatment and glass powder is not used.
[0046] The difference between Control Example 7 and Example 1 is that the preparation method adopted is: High-performance autoclaved aerated concrete preparation method: comprising the following steps: (1) Raw material pretreatment: pre-wetting the quartz sand to a moisture content of 10% (the water used is included in the water-cement ratio); (2) Mixing: mixing all the raw materials at the same time to obtain a slurry; (3) Molding: pouring the slurry into a mold and standing it at 60-65°C for 2 hours, demolding and cutting it into shape; (4) Steaming: sending the cut product into a steaming room to heat it to 180°C at 30-40°C / h, keeping it at a constant temperature for 8 hours at a pressure of 1.4-1.5 MPa, and then cooling it to room temperature at a rate of 15-20°C / h.
[0047] According to the national standard "Autoclaved Aerated Concrete Blocks", standard number GB / T11969-2020, standard specimens were made and tested, and the concrete properties obtained are shown in Table 2.
[0048] Table 2
[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high performance autoclaved aerated concrete, characterized in that: The method comprises the following raw materials in parts by weight: 25-35 parts of quartz sand, 18-22 parts of quicklime, 12-18 parts of cement, 3-5 parts of foaming agent, 5-8 parts of calcium borate powder, 0.1-0.3 parts of foam stabilizer and appropriate amount of water, with a water-cement ratio of 0.5-0.
55. The foaming agent is aluminum powder and silicon powder in a mass ratio of 3:(4-5).
2. The high performance autoclaved aerated concrete according to claim 1, characterized in that: The foaming agent is aluminum powder and silicon powder in a mass ratio of 3:
5. Aluminum powder pretreatment: take aluminum powder with a particle size of 50-100μm, then coat the aluminum powder with aluminum phosphate sol, dry it, and the coating layer thickness is 1-2μm; silicon powder pretreatment: wash and dry it with a 5% hydrochloric acid solution, then ball mill it to a particle size less than 200nm, and the volume ratio of silicon powder to hydrochloric acid solution is 0.
5.
3. The high performance autoclaved aerated concrete according to claim 2, characterized in that: The quicklime particle size is 50-100μm, and 30-40% of the quicklime is modified: the quicklime is coated with stearic acid and dried, and the coating thickness is 1-2μm; The colemanite powder has a particle size of 5-15 μm, is coated with a silane coupling agent, and is dried, with a coating layer thickness of 0.5-1 μm.
4. The high performance autoclaved aerated concrete according to claim 3, characterized in that: The cement is sulphoaluminate cement.
5. The high performance autoclaved aerated concrete according to claim 4, characterized in that: The invention comprises 5-10 parts of glass powder with a particle size of ≤10 μm.
6. The high performance autoclaved aerated concrete according to claim 5, characterized in that: The foam stabilizer is prepared by mixing sodium lauryl sulfate, hydroxypropyl methylcellulose and nano-SiO2 in a mass ratio of 1:0.5:0.
4.
7. The high performance autoclaved aerated concrete according to claim 6, characterized in that: The method comprises the following raw materials in parts by weight: 30 parts of quartz sand, 20 parts of quicklime, 15 parts of cement, 4.0 parts of foaming agent, 6.0 parts of calcium borate powder, 8.0 parts of glass micropowder, 0.2 parts of foam stabilizer and appropriate amount of water, with a water-cement ratio of 0.
52.
8. The high performance autoclaved aerated concrete according to claim 7, characterized in that: The aluminum phosphate sol is prepared by the following method: aluminum sulfate Al2(SO4)3 and sodium dihydrogen phosphate NaH2PO4 are used in a molar ratio of 1:6 to prepare an aluminum sulfate solution and a sodium dihydrogen phosphate aqueous solution respectively, and the sodium dihydrogen phosphate solution is slowly added dropwise to the aluminum sulfate solution while stirring, the pH value of the reaction system is controlled between 3 and 5, the reaction is carried out for 1 hour, the reaction is aged for 12 hours, and then the reaction is carried out with water and filtered to obtain the aluminum phosphate sol.
9. A process for preparing high performance autoclaved aerated concrete according to any one of claims 5 to 8, characterized in that: The method comprises the following steps: (1) raw material pretreatment: pre-wetting quartz sand to a moisture content of 8-12%, and activating colemanite powder at 105° C. for 2 hours; (2) mixing: mixing all raw materials to obtain slurry; (3) molding: pouring the slurry into a mold and leaving it at 82-85° C. for 2 hours, demolding and cutting into shape; and (4) steam curing: steam curing the cut product under high pressure.
10. The process for preparing high performance autoclaved aerated concrete according to claim 9, characterized in that: The step (2) of mixing is as follows: quartz sand, quicklime, cement, glass powder and colemanite are added in sequence, and dry mixed for 5 minutes, followed by adding silicon powder, foam stabilizer and water, and wet mixed for 8-10 minutes, and allowed to stand for 0.5 hours, and then adding aluminum powder and wet mixed for 5-8 minutes to obtain slurry; the step (4) of steam curing is as follows: the cut product is sent to a steam curing chamber and heated to 205°C at 30-40°C / h, maintained at a constant temperature for 8 hours at a pressure of 1.52-1.55MPa, and then cooled to room temperature at a rate of 12-13°C / h.
Citation Information
Patent Citations
Wear-resistant, antiknock and radiation-resistant concrete and preparation method thereof
CN105801040A
Aerated concrete gas-forming agent and aerated concrete
CN106380098A
B05-grade autoclaved aerated concrete block and preparation method thereof
CN108298892A
Grouting material for connecting steel bars in low temperature environment, and preparation method and application thereof
CN108314393A
Preparation method of autoclaved aerated concrete B07 anti-seepage building block
CN115140990A